A Case of Recurrent Cryptococcal Meningoencephalitis in an Immunocompetent Female - Negin Niknam; Negar Niknam; Kola Dushaj; Erfidia Restrepo (Case Reports in Infectious Diseases)
Cryptococcus neoformans is commonly associated with meningoencephalitis in immunocompromised patients and occasionally in apparently healthy individuals. Duration and regimen of antifungal treatment vary depending on the nature of the host and extent of disease and CNS shunts are placed in persistently elevated intracranial pressures. Recurrence of infection after initial treatment is not uncommon in HIV positive patients, Kaya et al. (2012) and Illnait-zaragozí et al. (2010). We describe a 39-year-old immunocompetent female that presented with neurologic deficits and increased intracranial pressure (ICP) due to cryptococcal meningoencephalitis that had a complicated course with drug induced hepatitis and persistently increased ICP that ultimately required shunt placement and presented again with relapse of cryptococcal meningoencephalitis after completion of antifungal treatment. Our case shows that recurrent cryptococcal meningitis can be seen in immunocompetent patients due to prolonged placement of CNS shunt and suggests that shunts should be removed after resolution of meningitis.